Replication, methylation, and expression of X laevis globin genes injected into fertilized Xenopus eggs. - Williams, J; Bendig, M; Patient, R; Banville, D; Greaves, D; Mahbubani, H (1983)
In the South African clawed toad, Xenopus laevis, the tadpole alpha-globin gene (alpha T1) and the major adult alpha- and beta-globin genes (alpha 1 and beta 1) are linked in the genome in the order alpha T1-alpha 1-beta 1. We show that cloned DNA fragments containing the Xenopus globin genes are replicated after injection into newly fertilized Xenopus eggs, reaching a maximal copy number at gastrulation. The DNA initially replicates as supercoils, but later it is found in a high-molecular-weight form, comigrating with the chromosomal DNA. In contrast to what has been found in mouse eggs, DNA does not become methylated when injected into Xenopus eggs. If, however, DNA is methylated in vitro before injection, methyl groups are retained through replication with a high efficiency. Both the adult alpha 1- and beta 1-globin genes are transcribed from their correct promoters in early embryonic stages, but the amount of transcription is relatively low and decreases in parallel with the decline in the amount of DNA retained in the embryo.